The adaptation of management control systems in sustainability-oriented innovation strategy implementation - Pan Fagerlin, Wen ; 0000-0002-4325-2684; Wen, Wenjun; Lövstål, Eva (Management Accounting Research, 2025)
Organizations are increasingly turning to sustainability-oriented innovation (SOI) to address pressing environmental and social challenges, yet implementation remains fraught with difficulties. Unlike incremental sustainability efforts, SOI embeds sustainability objectives into the core of innovation processes, encompassing products, services, and business models. This study investigates how the adaptation of management control systems (MCSs) enables the implementation of SOI. Drawing on a case study of a Scandinavian polyethylene-packaging firm responding to the European Union’s plastic ban by shifting to bio-based and recycled materials, we trace the firm’s rapid implementation of an SOI strategy. Leveraging Tessier and Otley’s (2012) refinement of Simons’ (1995) levers-of-control (LOC) framework, we show how the firm navigated distinct phases of SOI implementation by alternating between strategic and operational levels of control. Rather than developing entirely new control mechanisms, the firm adapted existing ones—a process we term plasticity, defined as the capacity to repurpose controls without altering their formal design or structure. This study advances research on management control for sustainability by introducing MCS plasticity as a key enabler of SOI and by demonstrating the analytical value of the revised LOC framework for examining complex sustainability transitions.